2014
DOI: 10.1016/j.bmcl.2014.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure–activity analysis of diphenylpyrazolodiazene inhibitors of the HIV-1 Nef virulence factor

Abstract: HIV-1 Nef is a critical AIDS progression factor yet underexplored target for antiretroviral drug discovery. A recent high-throughput screen for pharmacological inhibitors of Nef-dependent Src-family kinase activation identified a diphenylpyrazolodiazene hit compound with submicromolar potency in HIV-1 replication assays against a broad range of primary Nef variants. This compound, known as ‘B9’, binds directly to Nef and inhibits is dimerization in cells as a possible mechanism of action. Here were synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…[13] They exhibited ab road spectrum of biologicalp roperties such as antibacterial, [14] antifungal [15] and HIV-1 inhibitory activities. [16] In addition to pyrazoles,s everal methodsf or the synthesis of azopyra- zoles have been reported. [17] Most of these methods involve harsh operationsa nd multistep procedures throughr eactions of aryldiazonium salts with b-keto estersf ollowed by pyrazole formationu sing hydrazines.…”
Section: Introductionmentioning
confidence: 99%
“…[13] They exhibited ab road spectrum of biologicalp roperties such as antibacterial, [14] antifungal [15] and HIV-1 inhibitory activities. [16] In addition to pyrazoles,s everal methodsf or the synthesis of azopyra- zoles have been reported. [17] Most of these methods involve harsh operationsa nd multistep procedures throughr eactions of aryldiazonium salts with b-keto estersf ollowed by pyrazole formationu sing hydrazines.…”
Section: Introductionmentioning
confidence: 99%
“…1). 13 Recently, arylazopyrazoles have been widely used as important photoswitches offering quantitative isomerization 14 and light-responsive molecular switches in cyclodextrinbased supramolecular systems. 13 Recently, arylazopyrazoles have been widely used as important photoswitches offering quantitative isomerization 14 and light-responsive molecular switches in cyclodextrinbased supramolecular systems.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The original hit compound, referred to as ‘B9’, consists of a three-ringed structure with a diazene linker connecting a pyrazole core to a chlorophenyl group (compound 1 ; Table 1) 13 . This compound binds directly to recombinant Nef with a K D value in the nanomolar range, and inhibits Nef-dependent enhancement of HIV-1 infectivity and replication in vitro .…”
mentioning
confidence: 99%
“…Previous studies have shown that B9 (compound 1 ) inhibits Nef-dependent HIV-1 infectivity in this system and was included as a positive control. 12,13 Analogs with one- and two-carbon linkers (compounds 2 and 4 ) suppressed Nef-mediated enhancement of HIV-1 infectivity with IC 50 values of 0.69 μM and 3.54 μM, respectively (Table 1). These values agree favorably with results from the B9 parent compound, which yielded an IC 50 value of 2.53 μM.…”
mentioning
confidence: 99%
See 1 more Smart Citation